DEVISING AN INDONESIAN LEGAL ARCHITECTURE FOR METAVERSE BANKING: CHALLENGES AND OPPORTUNITIES - Kristianus Jimy Pratama (Journal of Central Banking Law and Institutions, 2023)
The objective of this research is to correct misconceptions about the metaverse and metaverse banking, as well as to refute national legal perspectives on metaverse banking. It is designed to also shed some light on challenges and opportunities connected to the plan of legal architecture on metaverse banking along with its supervision and enforcement mechanisms. Metaverse banking consists of banking activities in the metaverse ecosystem. Due to the rapid development of metaverse banking on a global level and unresponsive national regulations to govern it, there is no adequate legal regulation for this activity in Indonesia. The research method is normative through literature study. This research findings illustrate persistent errors about the concept of metaverse banking including the national legal authority’s perspective on the substance of regulation. The results also show that challenges and opportunities exist for devising a legal architecture on metaverse banking accompanied by a mechanism for supervision and dispute resolution. This research contributes to as well as serves as one of the references for study on metaverse banking in Indonesia